Enhanced Capture of Broadband Solar‐Blind UV Light via Introducing Alkali‐Metal Ions (Li+, Na+, and K+) into DC Spectral Converter. Issue 6 (28th December 2020) - Jia, Hong; Li, Xue; An, Ximei; Chang, Shasha; Liu, Zhongli; Peng, Feng; Liu, Xiaofeng; Gao, Linhui; Zhou, Shifeng; Qiu, Jianrong
Abstract: Rare earth doped down‐conversion (DC) materials, due to their unique spectral conversion characteristics, are promising candidates for narrow band solar‐blind ultraviolet (UV) light detection devices. Herein, an enhanced capture device for broadband solar‐blind UV light is constructed by combining an ordinary semiconductor with a DC spectrum converter, the essence of which is to introduce the appropriate alkali‐metal ions (Li +, Na +, and K + ) into DC layer. Europium‐doped organic–inorganic composite films are used as spectral converters because of their excellent DC characteristic, which can convert broadband solar‐blind UV incident illumination into visible light suitable for capture by light dependent resistor (LDR). Interestingly, the spectral conversion efficiency is positively correlated with the capture ability of broadband solar‐blind UV photons. The introduction of alkali‐metal ions in the DC layer enhances the photon detection efficiency with an increase rate of around 200%, which is attributed to alkali‐metal ions changing the local crystal field symmetry around the Eu 3+ emitter and distorting the matrix crystal of Y2 O3, thus increasing the probability of intra‐4 f electron transition. These results signify that the present rare‐earth doped DC luminescent materials are promising building blocks for assembly of high‐performance broadband solar‐blind UV detector. Abstract : An enhanced capture device for broadband solar‐blind ultraviolet (UV) light is constructed by combining an ordinary semiconductor with a down‐conversion (DC) spectrum converter, the essence of which is to introduce the appropriate alkali‐metal ions into DC layer. The result reveals a new avenue for the development of efficient broadband solar‐blind UV light detectors based on rare earth doped luminescent materials.